If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 2x = 6y Reorder the terms: 2x + 2y = 6y Solving 2x + 2y = 6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 2x + 2y + -2y = 6y + -2y Combine like terms: 2y + -2y = 0 2x + 0 = 6y + -2y 2x = 6y + -2y Combine like terms: 6y + -2y = 4y 2x = 4y Divide each side by '2'. x = 2y Simplifying x = 2y
| 3c+5=c+19 | | -2x+-3=-2x+-6 | | 0.3(21x-12)-(x+7)= | | 4b+2b=b+b+20 | | 4(1m-8)+8(1-8m)=-24 | | 10x+6=10x+3 | | 2=m-2-7 | | -78-x=-8x+20 | | 2(x+-1)=3(x+-4) | | 5x+9(9)=71 | | -70+6x=20+3x | | 2n-12=15n-129 | | 2(4+m)=10 | | (Y^2-3y-18)(3y+15)=0 | | 3-4(7x+5)=9 | | 40-(3x+4)=2(x+6)+x | | 52.8=4.4v | | 25=11+c+(2+c) | | X+2x+11=3 | | 8x+5=5x+-7 | | 4n=4+4 | | q+50=350 | | 7x*5x-1=12*2x+2 | | 7y-1=2(y+2)-2 | | 2-19=13 | | 5n=7+8 | | 9(-187)+160= | | 36n=36 | | 0.3+x=3.75 | | 10-4y=16 | | 12-3(2x+5y)= | | 8x-47=-x+61 |